P626 Safety of recombinant zoster vaccine in patients with Inflammatory Bowel Disease: a single centre experience. (30th January 2023) - Todeschini, A; Geccherle, A; Signoretto, P; Variola, A
Abstract: Background: Patients with inflammatory bowel disease (IBD) have an increased risk of herpes zoster (HZ) infection. However, vaccination rates for HZ are low among IBD patients. Although the safety of recombinant zoster vaccine (RZV) are high among immunocompetent individuals, there are only few data in IBD patients treated with immunomodulating drugs. This study aims to evaluate safety of recombinant zoster vaccine in IBD patients. Methods: This is a retrospective study among IBD patients after RZV vaccination. RZV was administrated to 31 IBD patients. Afterwards completed vaccination, telephone or in-person interviews were conducted to report adverse events (AEs) related to vaccination. Data on medical history and treatment was collected from electronic health records. Results: 32 patients, 12 CD and 20 UC, were enrolled. 77% received a complete RZV vaccination cycle. The vast majority of patients (97%) were in biological or immunomodulatory therapy and 80% had previous HZ infection. About 30% of patients had at least one side effect. Local pain at site of injection (27%) and fever (47%) were the most common AEs. Flares of the underlying IBD were not reported. The vast majority of AE were mild and lasted only a few days. No serious AEs were reported. Conclusion: The short-term vaccine reactions experienced in this cohort of IBD patients were self-limited, including local pain at the injection site and fever. We found a good safety profile of RZV vaccination in our cohort.